2001
DOI: 10.1007/s004420100736
|View full text |Cite
|
Sign up to set email alerts
|

The growth response of plants to elevated CO2 under non-optimal environmental conditions

Abstract: Under benign environmental conditions, plant growth is generally stimulated by elevated atmospheric CO concentrations. When environmental conditions become sub- or supra-optimal for growth, changes in the biomass enhancement ratio (BER; total plant biomass at elevated CO divided by plant biomass at the current CO level) may occur. We analysed literature sources that studied CO×environment interactions on the growth of herbaceous species and tree seedlings during the vegetative phase. For each experiment we cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(120 citation statements)
references
References 53 publications
15
101
3
1
Order By: Relevance
“…If CO 2 inhibition of shoot NO 3 Ϫ assimilation were common among C 3 species, it could account for several responses of plants to elevated CO 2 , including the decline in shoot protein and the diminished activities of photosynthetic enzymes. Nitrogen availability determines plant responses to elevated CO 2 concentrations more than any other environmental factor (52,53), but ecosystems show a broad range of responses to elevated CO 2 concentrations, possibly as a result of the seasonal and spatial fluctuations in the relative availabilities of NH 4 ϩ and NO 3 Ϫ . For instance, ecosystems in which NH 4 ϩ is the dominant nitrogen form, such as pine forests (54) or wetlands (55), show a relatively large increase (Ϸ25%) in net primary productivity under CO 2 enrichment, whereas ecosystems in which NO 3 Ϫ is dominant, such as grasslands (56) or wheat fields, at standard fertilizer levels (low fertilizer treatment at Maricopa, AZ; ref.…”
Section: Discussionmentioning
confidence: 99%
“…If CO 2 inhibition of shoot NO 3 Ϫ assimilation were common among C 3 species, it could account for several responses of plants to elevated CO 2 , including the decline in shoot protein and the diminished activities of photosynthetic enzymes. Nitrogen availability determines plant responses to elevated CO 2 concentrations more than any other environmental factor (52,53), but ecosystems show a broad range of responses to elevated CO 2 concentrations, possibly as a result of the seasonal and spatial fluctuations in the relative availabilities of NH 4 ϩ and NO 3 Ϫ . For instance, ecosystems in which NH 4 ϩ is the dominant nitrogen form, such as pine forests (54) or wetlands (55), show a relatively large increase (Ϸ25%) in net primary productivity under CO 2 enrichment, whereas ecosystems in which NO 3 Ϫ is dominant, such as grasslands (56) or wheat fields, at standard fertilizer levels (low fertilizer treatment at Maricopa, AZ; ref.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports showed that the magnitude of the plant growth response to elevated CO 2 may vary greatly depending on soil nutrients conditions (Stitt and Krapp, 1999;Poorter and Perez-Soba, 2001). Our experiment showed larger losses of mineral nutrients (K + , Ca 2+ and Mg 2+ ) under elevated atmospheric CO 2 concentrations in subtropical China.…”
Section: Nitrogen Leaching Lossesmentioning
confidence: 99%
“…Interactions between CO 2 and N varied between experiments [28], but it is often accepted that only with non-deficient N availability, elevated CO 2 can stimulate growth and biomass production [25,30,32,41]. Previous findings from the POP-FACE study (the present EUROFACE study) showed that FACE enhanced the optical LAI of the high density plantation in the first year and in spring of the second year after planting as a result of a stimulation of individual leaf area and tree dimensions [12].…”
Section: Introductionmentioning
confidence: 99%